STUDY ON VIBRATION CHARACTERISTICS OF THE POLYGON EFFECT OF SCRAPER CONVEYOR - ZHANG DongSheng; YU HaiYang; ZHAO XiBei; SONG ZhenDuo (Jixie qiangdu)
Scraper conveyor chain and chain gear transmission as the research object,analysis of the scraper conveyor load and no-load conditions chain dynamics,and numerical simulation of the scraper conveyor special point chain speed and tension are simulated. The results showed that: the most important parameter of the chain is the number of sprocket teeth,and the running stability of the scraper conveyor is proportional to the number of sprocket teeth,13 tooth sprocket stability is far stronger than 9 tooth sprocket scraper conveyor; polygon effect there side impact load on the chain tension fluctuation significantly higher than the no-load side; the reaction sensitivity of polygon effect is inversely proportional to the length of the chain length of the scraper conveyor and sprocket selection provides a theoretical basis,and to Study on dynamic characteristics of research methods and provides a theoretical basis.